2021
DOI: 10.3389/fphys.2021.729452
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial tRNA-Derived Fragments and Their Contribution to Gene Expression Regulation

Abstract: Mutations in human mitochondrial tRNAs (mt-tRNAs) are responsible for several and sometimes severe clinical phenotypes, classified among mitochondrial diseases. In addition, post-transcriptional modifications of mt-tRNAs in correlation with several stress signals can affect their stability similarly to what has been described for their nuclear-encoded counterparts. Many of the perturbations related to either point mutations or aberrant modifications of mt-tRNAs can lead to specific cleavage and the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…71,72 More research is needed to determine the whole plethora of retrograde stimuli in addition to the decrease in mitochondrial potential, free radicals, and a decrease in ATP level. In higher eukaryotes it was reported that calcium concentration, 73 Krebs cycle metabolites, 74 mitochondrial-derived peptides, 45,46 and recently ncRNA (non-coding RNA) 75,76 including mt-tRF (mitochondrial tRNA-derived fragments) 77,78 facilitate signaling to the nucleus in response to mitochondrial damage. It is among the most pressing questions to describe the exact role of the triggers mentioned above in yeast.…”
Section: Retrograde Regulation Of the Rtg Pathway Beyond S Cerevisiaementioning
confidence: 99%
“…71,72 More research is needed to determine the whole plethora of retrograde stimuli in addition to the decrease in mitochondrial potential, free radicals, and a decrease in ATP level. In higher eukaryotes it was reported that calcium concentration, 73 Krebs cycle metabolites, 74 mitochondrial-derived peptides, 45,46 and recently ncRNA (non-coding RNA) 75,76 including mt-tRF (mitochondrial tRNA-derived fragments) 77,78 facilitate signaling to the nucleus in response to mitochondrial damage. It is among the most pressing questions to describe the exact role of the triggers mentioned above in yeast.…”
Section: Retrograde Regulation Of the Rtg Pathway Beyond S Cerevisiaementioning
confidence: 99%
“…Stress signals can also affect the stability of mitochondrial tRNAs leading to their cleavage and the production of mitochondrial tRFs (mt-tRFs). Several mt-tRFs are produced because of the excessive mitochondrial stress affecting mitochondrial DNA integrity [ 179 ].…”
Section: Trna-derived Small Rnasmentioning
confidence: 99%
“…15,16 Interestingly, a substantial proportion of tRFs arises from mitochondrial tRNAs (mt-tRNAs) and are actively implicated in tumorigenesis and cancer progression, primarily through their role in perturbing translation and mitochondrial metabolism. 17,18 Herein, we have investigated tRF profiles in association with MM and benign disease states (MGUS/sMM), aiming to reveal potential MM-related tRFs of clinical significance.…”
Section: Introductionmentioning
confidence: 99%
“…tRFs play pivotal roles in regulating gene expression, acting in a miRNA‐like manner and affecting numerous biological processes, including cell proliferation, migration and apoptosis 15,16 . Interestingly, a substantial proportion of tRFs arises from mitochondrial tRNAs (mt‐tRNAs) and are actively implicated in tumorigenesis and cancer progression, primarily through their role in perturbing translation and mitochondrial metabolism 17,18 …”
Section: Introductionmentioning
confidence: 99%